The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10623-020-00750-x
|View full text |Cite
|
Sign up to set email alerts
|

A geometric approach to rank metric codes and a classification of constant weight codes

Abstract: In this work we develop a geometric approach to the study of rank metric codes. Using this method, we introduce a simpler definition for generalized rank weight of linear codes. We give a complete classification of constant rank weight code and we give their generalized rank weights. *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 27 publications
3
54
0
Order By: Relevance
“…This connection has been intensively used to get classification results and intriguing constructions in both the areas of coding theory and finite geometry. Recently, in [38,41] it has been shown that equivalence classes of nondegenerate rank-metric codes are in one-to-one correspondence with equivalence classes of q-systems, where the latter constitute the q-analogue of projective systems; see also [1]. At this point, it is natural to ask whether it is possible to construct geometric objects able to capture the structure of sum-rank metric codes which generalize both projective systems and q-systems.…”
Section: Geometry Of Sum-rank Metric Codesmentioning
confidence: 99%
See 1 more Smart Citation
“…This connection has been intensively used to get classification results and intriguing constructions in both the areas of coding theory and finite geometry. Recently, in [38,41] it has been shown that equivalence classes of nondegenerate rank-metric codes are in one-to-one correspondence with equivalence classes of q-systems, where the latter constitute the q-analogue of projective systems; see also [1]. At this point, it is natural to ask whether it is possible to construct geometric objects able to capture the structure of sum-rank metric codes which generalize both projective systems and q-systems.…”
Section: Geometry Of Sum-rank Metric Codesmentioning
confidence: 99%
“…More recently a similar geometric approach was used for codes in the rank metric. A first intuition was given in [40], while a full correspondence was provided in [41] and in [38]: kdimensional rank-metric codes over an extension field F q m of F q correspond to q-systems, which are special F q -subspaces of F k q m . This correspondence allowed us to give a complete characterization of nondegenerate F q m -linear one-weight codes in the rank metric; see [38,Theorem 12], [1,Proposition 3.16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in [24] Randrianarisoa introduced q-systems. A q-system U over q n  with parameters m r d [ , , ] is an m-dimensional q  -subspace generating over q n  a r-dimensional q n  -vector space V , where…”
mentioning
confidence: 99%
“…]-rank metric codes, cf. [24,Theorem 2]. In [10] the authors investigated the following subspace analogue of caps of kind h: for h r…”
mentioning
confidence: 99%
“…Let G be a matrix in F r× rn 2 q m whose columns are a basis of U . As a consequence of Theorem 7.16 and the connection between linear rank metric codes and q-systems (see [28] and also [1]), the linear rank metric codes having as a generator matrix G have exactly three nonzero weights, which are n − r, n − 1, n. In particular, they are examples (r − 1)-almost MRD codes, see [12]. Moreover, using [1, Theorem 4.8], we can from L U we can also construct linear Hamming metric codes with only three weight and for which we can completely establish its weight distribution, as already done for some classes of linear sets (see also [25,33]).…”
Section: More Preciselymentioning
confidence: 97%